The possible role of waqf in ensuring a sustainable Malaysian Federal Government debt - Azrai Azaimi Ambrose, Azniza Hartini; Aslam, Mohamed; Hanafi, Hanira (Elsevier B.V., 2015)
This paper attempts to investigate waqf as a possible instrument to reduce the Malaysian Federal Government debt. The latest Malaysian federal government debt to gross domestic product (GDP) ratio is 54.47%; more than the 50% threshold for developing economies. This increasing debt level will hurt the economy in the long run. In an effort to reduce the debt, the Malaysian government is presently selling government assets and reforming the taxation system i.e. by introducing Goods and Sales Tax (GST) on 1st April 2015. We however notice that there is an alternative solution from Islamic economics which complies with the Shari’ah law. The alternative is waqf. This paper provides a conceptual framework of the possibility of waqf with respect to its role in federal government debt sustainability. Firstly, the aspect at which waqf can contribute to federal government debt reduction is presented. Secondly, the study discusses the Shari’ah law of waqf, its contemporary issues and the management of waqf in Malaysia. Since Malaysia is a multi-religion society consisting of Muslims and non-Muslims alike, we also analyse the Shari’ah law of waqf pertaining to the non-Muslims. Finally, this paper offers suggestion of a waqf model that may be able to manage and control the federal government debt from ballooning.